Seminar UMKM Go Export Bersama Bank Sumsel Babel 2025 - M Arief Rahman; Ade Silvia Handayani; Dewi Ekha Harlasyanti; Ella Rosita; Ambar Sehatiningsih (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) hold a strategic role in the national economy but continue to face challenges in accessing international markets, securing funding, managing legal compliance, and understanding export procedures. The UMKM Go Export Seminar with Bank Sumsel Babel 2025 was conducted to strengthen the capacity of MSME actors to penetrate the global market, featuring speaker Dewi Ekha Harlasyanti, S.H. This activity aimed to provide knowledge on export strategies for local products, optimization of digital marketing, legal business management, and appropriate product packaging for export standards. The seminar was conducted using a descriptive qualitative observational method through discussion sessions, material presentations, and participant satisfaction evaluations. The target audience consisted of MSMEs in the South Sumatra, focusing on improving product competitiveness for export purposes. The seminar resulted in increased understanding among participants regarding small-scale export opportunities, flexible payment systems, strategies for finding international buyers through social media, and the importance of mastering product specifications. The involvement of Bank Sumsel Babel in offering financial support further facilitated better access to capital for MSMEs. This activity contributed to improving the readiness of local MSMEs to initiate the export process progressively, thereby enhancing the region’s product contribution to global trade.